ENSURING THE REALIZATION OF THE RIGHTS OF INTERNALLY DISPLACED PERSONS AND RESIDENTS OF THE OCCUPIED AND UNCONTROLLED TERRITORIES OF UKRAINE FOR EDUCATION: PUBLIC-MANAGEMENT ASPECT - Postupna O.V.; Polyakova O.S. (Pressing Problems of Public Administration, 2018)
The article analyzes the state of ensuring the implementation of the right of internally displaced persons and residents of the occupied and uncontrolled territories of Ukraine for education, identifies the main problems that are still unsolved or which mechanisms of resolution are imperfect. Those problems that can become serious challenges for Ukrainian society in the future if they are not being solved today are highlighted.